Upaya Memelihara Budaya Bersih Lingkungan Sekolah Melalui Metode Pembinaan Kepala Sekolah SMA Negeri 1 Terara - Samsul Mujtahid (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
This study intends to reveal the problem of "Efforts to Maintain a Clean Culture of the School Environment Through the Principal Guidance Method of SMA Negeri 1 Terara" identifying a clean environment culture through programmed coaching methods namely, habituation, exemplary, joint movement. This study uses a descriptive qualitative approach. The data subjects of this study were homeroom teachers, students, picket teachers consisting of three classes as research samples, namely class X IPS3 XI MIPA 2, and XII IPS 5 at SMA Negeri 1 Terara. Data was collected through observation sheets and interview sheets. Based on the results of data analysis that has been carried out in the Efforts to Maintain a Clean Culture of the School Environment Through the Programmed Development Method the Principal of SMA Negeri 1 Terara can be concluded, based on the results of the analysis of cycles I and II show results. In the first cycle, the observation of maintaining a clean culture reached a score of 21%. Then, the interview part in cycle I. The homeroom teacher interview showed an average score of 33%. Furthermore, the results of the student interviews averaged a score of 26%. While interviewing picket teachers, the average score was 33%. Then, after conducting coaching through inculcating habits, exemplary, and moving together. In cycle II continued the results. In the observation section of the second cycle, the average final score was 64%. Next is the interview section in cycle II. Homeroom teacher interviews show an average score of 80%. Furthermore, the results of the student interviews averaged a score of 73%. While interviewing picket teachers, the average score was 80%. Based on the average value of cycle I and cycle II, there was an increase in maintaining a clean culture of the school environment through the programmed coaching method of the principal of SMA Negeri 1 Terara as a research subject.